Analisis Teknik Dasar Pencak Silat PSHT Rayon Lubuk Kupang Ranting Lubuklinggau Selatan 1 - Chrisdianto, M; Satinem, Y; Suhdy, M (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
This study aims to describe the basic techniques of pencak silat PSHT Lubuk Kupang Branch Lubuklinggau Selatan 1. This research is a type of qualitative descriptive research. The subjects of this study were trainers and students of pencak silat PSHT Rayon Lubuk Kupang. Data collection techniques were carried out by interview, observation, and documentation. Data were analyzed using components recommended by Miles and Huberman. Data collection was carried out at night after the data collected were immediately analyzed. The results showed that the value of the movement in the basic technique of limb attack was seen when the researchers made observations. The basic limb attack technique research describes the total number of 7 students who have been observed one by one and are said to be able to perform the basic limb attack technique correctly and accordingly. That the results of this study indicate that the movement on the basic techniques of limb attack pencak silat PSHT rayon Lubuk Kupang Branch Lubuklinggau Selatan 1 is categorized as good.